Permasalahan Sarana dan Prasarana di Sekolah Dasar - Naila Zahra; Malik Al Jabar; Angela Meryci Vina Ganendra; Ghozi Albari; Sri Suwartini (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
Educational facilities and infrastructure play a crucial role in supporting the success of the learning process in elementary schools. Facilities include learning tools and media, while infrastructure refers to classrooms, libraries, laboratories, and other supporting facilities. The availability of adequate facilities and infrastructure can enhance students’ comfort, motivation, and learning outcomes. Conversely, limited resources may hinder teachers’ performance, reduce students’ learning enthusiasm, and widen educational quality gaps. Therefore, improving the quality of facilities and infrastructure through equitable distribution, proper maintenance, and collaborative efforts is essential to ensure an effective, efficient, and enjoyable learning process.